Optical Radiation of Electrons and Positrons at Quasi-Molecular Channeling in Crystals; Physica Status Solidi (B): Basic Research; Vol. 143, iss. 2 - Popov D. E.; Rozum E. I.; Savushkin S. E.; Uglov S. R. Sergey Romanovich; Vorobiev S. A. Sergey Aleksandrovich (1987, 1987)
Title screen